A new energy‐based method to evaluate low‐cycle fatigue damage of AISI H11 at elevated temperature. Issue 6 (5th January 2017) - Du, W; Luo, Y; Wang, Y; Chen, S; Yu, D
Abstract: AISI H11 (X38CrMoV5‐1) hot‐work tool steel is widely used for making extrusion tools because of its good mechanical properties at high temperature and moderate cost. To predict its lifetime, an energy conservation‐based model was proposed in this paper by introducing the damage rate, which is expressed as the product of damage force and plastic strain rate. The strain‐controlled low‐cycle fatigue tests were conducted to obtain the parameters of the proposed model, while the stress‐controlled low‐cycle fatigue tests were used to validate the proposed model. The results demonstrate that the proposed model is accurate and reliable. Furthermore, the local misorientation was investigated by electron backscatter diffraction to analyse the correlation between the microstructure evolution and the cyclic behaviour, and crack propagation behaviour was identified.